Infectious agents in coronary atheromas: a possible role in the pathogenesis of plaque rupture and acute myocardial infarction - HIGUCHI Maria de Lourdes; RAMIRES Jose A. F. (Universidade de São Paulo (USP), 2002)
In this review we report our recent findings of histopathological features of plaque instability and the association with Mycoplasma pneumoniae (MP) and Chlamydia pneumoniae (CP) infection, studying thrombosed coronary artery segments (CAS) of patients who died due to acute myocardial infarction. Vulnerable plaques are known to be associated with fat atheromas and inflammation of the plaque. Here we demonstrated that vulnerability is also related with focal positive vessel remodeling that maintains relatively well preserved lumen even in the presence of large atheromatous plaques. This phenomena may explain why the cinecoronariography may not detect large and dangerous vulnerable plaques. Greater amount of these bacteria in vulnerable plaques is associated with adventitial inflammation and positive vessel remodeling: the mean numbers of lymphocytes were significantly higher in adventitia than in the plaque, good direct correlation was obtained between numbers of CD20 B cells and numbers of CP infected cells in adventitia, and between % area of MP-DNA in the plaque and cross sectional area of the vessel, suggesting a cause-effect relationship. Mycoplasma is a bacterium that needs cholesterol for proliferation and may increase virulence of other infectious agents. In conclusion, co-infection by Mycoplasma pneumoniae and Chlamydia pneumoniae may represent an important co-factor for plaque instability, leading to coronary plaque thrombosis and acute myocardial infarction, since larger amount of these bacteria strongly correlated with histological signs of more vulnerability of the plaque. The search of CMV and Helicobacter pilori in these tissues resulted negative.